INCREASING COMMUNITY KNOWLEDGE ABOUT HYPERTENSION THROUGH HEALTH EDUCATION - Inta Susanti; Dwiky Andreansyah; Robiatul Wafiroh; Nanda Halimatus sya'diyah; Fransiska Diah A. (Journal of Community Research and Engagement, 2024)
Hypertension is a major health problem that is often experienced by the elderly and can cause serious complications if not managed properly. With the increasing elderly population, the knowledge of the elderly about hypertension are by providing direct health examinations and counseling. The subjects in this community service are the elderly who live in Bugel Village, Sekaran District, Lamongan Regency. The community service method is in the form of examination and counseling using leaflets and posters. The health examination instrument used in this activity is a hypertension examination using a digital tensiometer. The results of community service obtained elderly people who suffer from hypertension are 11% male and 31% female. In conclusion, examination and counseling regarding hypertension in the elderly have a crucial role in increasing the awareness and knowledge of the elderly about this condition. It is hoped that there will be a follow-up from this activity and a special concern for related agencies in providing a preventive role for the elderly.